Childhood trauma as a risk factor for psychosis: A sib-pair study. (November 2015) - Barrigón, María Luisa; Diaz, Francisco J.; Gurpegui, Manuel; Ferrin, Maite; Salcedo, María Dolores; Moreno-Granados, Josefa; Cervilla, Jorge A.; Ruiz-Veguilla, Miguel
Abstract: Background: Childhood trauma, cannabis use and certain personality traits have been related to the development of psychosis. This study uses a sib-pair design to examine the association between childhood trauma and psychosis controlling for cannabis use and neuroticism. Methods: We evaluated 60 patient-sibling pairs, conformed by patients with functional psychosis in the first five years of their illness matched with a non-psychotic sibling. In univariate analyses, patients and siblings were compared with McNemar tests and paired-sample t tests. A conditional logistic regression model of the risk of developing psychosis was built. The dependent variable of this model was the patient-sibling status (patient = 1, sibling = 0). Results: After controlling for cannabis use and neuroticism, the odds of suffering psychosis for subjects who experienced a childhood trauma were 7.3 times higher than the odds for subjects who did not experience a childhood trauma [95% CI, (1.06–50.01); P = 0.04]. Also, after controlling for experiencing childhood trauma and neuroticism, subjects who were heavy cannabis users had odds of suffering psychosis that were 6.4 times higher than the odds of the remaining subjects [95% CI, (1.2–35.2); P = 0.03]. Conclusion: Both childhood trauma and cannabis use were significantly associated with an increased risk of suffering functional psychosis. A neurotic personality also contributed independently to this risk. These findings might help improve the prevention of psychosis and the development of specific treatment strategies on this specific population. Highlights: A sib-pair study into patients with recent onset psychotic illness and their non-psychotic siblings was conducted. After controlling for cannabis use and neuroticism, childhood trauma was related to an increased risk of psychosis. Childhood trauma, cannabis use and neuroticism were independently associated with an increased risk of psychosis.